2022
DOI: 10.1111/jora.12740
|View full text |Cite
|
Sign up to set email alerts
|

Lessons of Resistance from Black Mothers to their Black Sons

Abstract: In negotiating the anti-Black oppression, Black mothers communicate lessons of resistance in their racial socialization messages to their Black adolescent boys. We investigate whether distinct strategies of resistance for survival, characterized by individual-focused immediate strategies of resistance, and resistance for liberation, strategies of resistance that disrupt systems of anti-Black oppression rooted in furthering collective Black empowerment, are employed in Black mothers' messages to their sons. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Das et al. (2022, this volume) also answered the call for considering resistance broadly in this special section. Drawing on Robinson and Ward’s (1991) work, Das et al.…”
Section: Expanding the Conceptualization Of Resistancementioning
confidence: 84%
“…Das et al. (2022, this volume) also answered the call for considering resistance broadly in this special section. Drawing on Robinson and Ward’s (1991) work, Das et al.…”
Section: Expanding the Conceptualization Of Resistancementioning
confidence: 84%
“…Particularly, Das et al. (2022) demonstrate that Black mothers in their study were more likely to communicate resistance for survival strategies to their sons, which are individual‐focused and short‐term responses to oppression that are sometimes necessary to survive but can also reinforce existing hierarchies as these strategies do not challenge the status quo. Although studies have shown mixed results for the relationship between preparation for bias and youth outcomes, resistance for survival preparation is associated with more negative outcomes such as depression and lower academic grades (Das et al., 2022; Rogers & Way, 2018).…”
Section: Reframing Youth Behavior As Resistance To Systemic Marginali...mentioning
confidence: 91%
“…Das et al (2022), for example, noted that the majority of African American mothers in their sample who engaged in preparation for bias did so to promote resistance for survival (e.g., self-patrolling, ignoring discrimination, focusing on hard work). Adding to this school of thought, Das et al (2022) also observed that preparation for bias may also foster resistance for liberation (e.g., self-advocacy, building critical consciousness, affirming their African American identity, and racial pride). Further, patterns of both resilience and resistance in parental racial socialization conversations with their children (Das et al, 2022).…”
Section: Resilience and Resistance Are Not The Samementioning
confidence: 99%